DIGITAL DA'WAH AND RELIGIOUS UNDERSTANDING AMONG THE INSTAGRAM FOLLOWERS OF @tebuireng.online - Nadin Kharisma; Anwari (Universitas Islam Negeri Mataram, 2026)
The dynamics of da’wah in digital spaces have transformed the way society obtains and constructs religious understanding. This study is important for analyzing the characteristics of digital da’wah content on the Instagram account @tebuireng.online and the process through which followers’ religious understanding is formed. This research employs a qualitative method using a case study approach and reception analysis, conducted through digital observation and in-depth interviews with followers of the @tebuireng.online account. The findings show that the da’wah content is dominated by the Reels format, characterized by attractive visuals, communicative language, and material that is relevant to everyday life. Followers interpret the content as a source of religious knowledge, a reinforcement of spirituality, and a practical reference for socio-religious life.